Combined Rothia dentocariosa and Streptococcus viridans Corneal Ulcer in an Immunocompromised Patient. (16th November 2021) - Dietze, Jamie; Mauger, Thomas
Abstract : Keratitis is a very common condition seen by ophthalmologists. However, many factors can complicate the treatment of this depending on the causative organism and other patient comorbid conditions. The objective of this clinical case report is to highlight the treatment of keratitis caused by Rothia dentocariosa . It also looks at the unique considerations in keratitis presentations for patients immunocompromised by chemotherapy agents. Our patient is a 58 yo female undergoing chemotherapy with folinic acid, fluorouracil, irinotecan, and panitumumab who presented with several days of a red, painful right eye with mucous discharge. Cultures were positive for Rothia dentocariosa and Streptococcus viridans . The patient ultimately underwent a conjunctival flap procedure as medical therapy with proper oral and topical antibiotics failed to resolve keratitis. This case is unique as previously, only a couple of cases of keratitis caused by Rothia dentocariosa have been reported and none of those patients were immunocompromised nor failed antibiotic therapy.